2012
DOI: 10.4415/ann_12_04_12
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine preventable viral diseases and risks associated with waterborne transmission

Abstract: Abstract. Rotavirus and poliovirus are paradigmatic viruses for causing major diseases affecting the human population. The impact of poliovirus is remarkably diminished because of vaccination during the last half century. Poliomyelitis due to wild polio currently affects a limited number of countries, and since 2000 sporadic outbreaks have been associated to neurovirulent vaccine-derived polioviruses. Conversely, rotavirus is presently very diffuse, accounting for the largest fraction of severe gastroenteritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 74 publications
(122 reference statements)
1
7
0
Order By: Relevance
“…The environmental surveillance in Milan undertaken between 2006 and 2010 showed the presence of HEVs in 80% of wastewater samples. This result is in agreement with data from other studies conducted in Italy (Cesari et al 2010;Ruggeri and Fiore 2012) and other countries (Cost an-Longares et al 2008;Kargar et al 2009). The difference in the detection frequency of the HEVs among the three sampling sites appeared to be significant only in 2006, at Nosedo, which showed a lower percentage of HEVs than the other two sites (P < 0Á01), whereas, in 2007, a statistically significant decrease (P < 0Á02) in the frequency of the total number of viral isolates occurred with respect to the other years.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The environmental surveillance in Milan undertaken between 2006 and 2010 showed the presence of HEVs in 80% of wastewater samples. This result is in agreement with data from other studies conducted in Italy (Cesari et al 2010;Ruggeri and Fiore 2012) and other countries (Cost an-Longares et al 2008;Kargar et al 2009). The difference in the detection frequency of the HEVs among the three sampling sites appeared to be significant only in 2006, at Nosedo, which showed a lower percentage of HEVs than the other two sites (P < 0Á01), whereas, in 2007, a statistically significant decrease (P < 0Á02) in the frequency of the total number of viral isolates occurred with respect to the other years.…”
Section: Discussionsupporting
confidence: 94%
“…Since in Italy, the full IPV Salk schedule was introduced in 2002, the isolation of PVs is presumably explained by the presence of individuals (children or adults) coming from countries where vaccination with OPV is still in use. However, there were no wild poliovirus (WPV) detections in the raw sewage samples examined, as it was to be expected in a 'polio-free' certified country; the identification of 2 PV-SLs demonstrated that the risk of virus reintroduction (wild or Sabin) is an event that is always possible due to globalization and continuous movement of the population, which creates frequent contacts with individuals from countries still using OPV vaccines or immigrants from countries where PV still is endemic (Gary et al 2007;Zurbriggen et al 2008;Ruggeri and Fiore 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…No wild polioviruses were isolated from the environmental samples examined during the study period, supporting the epidemiological data deriving from AFP surveillance (6,7,59).…”
Section: Discussionmentioning
confidence: 51%
“…Environmental surveillance has been widely used for the detection of disease outbreaks, in disease reduction and as indicators for early warning systems and for source attribution [180,181,182,183,184,185,186]. The institution and data source platform are summarized into the Table 3.…”
Section: Resultsmentioning
confidence: 99%